CONCRETE APPROACH TO THE FORMATION OF ISLAMIC HISTORIOGRAPHY - Hajibabaee, Majid (European Scientific Journal, ESJ, 2014)
Historiography is one of the fields that are considered in historical studies. Understanding of historiography is possible from the various approaches. One of the approaches that we can use in historical studies is â€œconcrete approachâ€. The concrete approach means we consider environmental situation in analyses. Historical phenomena are formed in interaction with other aspects of human life and not a single field. Islamic historiography in this paper studied with concrete approach. It means Islamic historiography formed in the social context and historical developments. The question is what circumstances led to notice to science of History after the establishment and spread of Islam in the world. Answering this question will be studied the various aspects of political, social and cultural Muslim Life. Especially the civilizations that have been conquered by Muslims will be discussed. The end of this article also will be discussed the characteristics of Islamic historiography and will be considered the four elements: 1- the religious View 2-Identity 3- Reproduction of power in the text 4- history as Political phenomenon.